2008
DOI: 10.1029/2007gl032048
|View full text |Cite
|
Sign up to set email alerts
|

Injection of a bubble into the inner magnetosphere

Abstract: [1] Magnetic reconnection in the magnetotail or other forms of current sheet disruption are believed to produce plasma bubbles, which consist of flux tubes that have lower entropy content PV 5/3 than their surroundings. We present an initial Rice-Convection-Model-based simulation of the injection of a bubble into the inner magnetosphere and explore the consequences on ring current formation. As the bubble moves into the inner magnetosphere, region-1-sense Birkeland currents form along its eastward and westward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 20 publications
3
48
0
Order By: Relevance
“…The flux tubes immediately earthward of the bubbles are pushed inward by the bubbles. They are the other element that also plays an important role in the pressure buildup [Zhang et al, 2008;Yang et al, 2011]. The electric field that is concentrated inside a bubble channel leaks out at the head of the bubble, which yields strong earthward E × B drift velocity there.…”
Section: 1002/2015ja021398mentioning
confidence: 99%
See 1 more Smart Citation
“…The flux tubes immediately earthward of the bubbles are pushed inward by the bubbles. They are the other element that also plays an important role in the pressure buildup [Zhang et al, 2008;Yang et al, 2011]. The electric field that is concentrated inside a bubble channel leaks out at the head of the bubble, which yields strong earthward E × B drift velocity there.…”
Section: 1002/2015ja021398mentioning
confidence: 99%
“…In recent years, the Rice Convection Model (RCM) and the Rice Convection Model-Equilibrium (RCM-E) have been extensively used to investigate how the plasma inside depleted flux tubes is transported in the nearEarth region [Lemon et al, 2004;Zhang et al, 2008;Zhang et al, 2009aZhang et al, , 2009bYang et al, 2008Yang et al, , 2011Yang et al, , 2012Yang et al, , 2014aYang et al, , 2014b. The model uses the slow-flow approximation and assumes an isotropic pressure distribution along magnetic field lines.…”
Section: Introductionmentioning
confidence: 99%
“…V ⊥ ) measured by C3 points at TC-2, increasing confidence that the feature observed by Cluster is the same as that detected by TC-2. Simulations have studied the features of a depleted flux tube that might be expected close to the Earth (Birn et al, 2004), and the effect the presence of a depleted flux tube might have on the inner magnetosphere (Zhang et al, 2008), although to date no plasma bubbles have been detected at X GSM >−8 R E . Birn et al (2004) predicted that, close to the Earth, after sufficient time had passed since the creation of a depleted flux tube, the plasma depletion and commensurate increase in magnetic pressure that characterise a plasma bubble actually reverse -field-aligned flows from further downtail transport plasma to the higher latitude, near-Earth region, increasing the local plasma pressure.…”
Section: Tc-2 Datamentioning
confidence: 99%
“…[4] Here, we describe the setup of a more sophisticated substorm-associated bubble simulation that extends the work of Zhang et al [2008]. We focus on an observed substorm instead of an idealized one, and tailor RCM inputs for consistency with Geotail measurements on 22 July 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Lemon et al [2004] showed that even strong convection could not force loaded flux tubes characterized by growth-phase plasma sheet values of the entropy parameter PV 5/3 to drift onto quasi-dipolar inner magnetosphere flux tubes, while flux tubes with reduced values of PV 5/3 could do so. Zhang et al [2008] used the Rice Convection Model (RCM) to examine the process by which reduced content plasma-sheet bubbles could result in a pressure increase in the ring current region.…”
Section: Introductionmentioning
confidence: 99%